2021
DOI: 10.1177/10775595211029713
|View full text |Cite
|
Sign up to set email alerts
|

Child Welfare System Involvement Among Children With Medical Complexity

Abstract: Children with medical complexity may be at elevated risk of experiencing child maltreatment and child welfare system involvement, though empirical data are limited. This study examined the extent of child welfare system involvement among children with medical complexity and investigated associated health and social factors. A retrospective chart review of children with medical complexity (N = 208) followed at a pediatric hospital-based complex care program in Canada was conducted. Descriptive statistics and od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…It should be noted that very few studies have assessed ACSCs for children who have possibly experienced maltreatment, and this issue needs to be investigated further in other samples (e.g., children involved in child protective services). Relative to the general pediatric population, children with suspected maltreatment have more chronic illnesses and higher medical complexity (Azzopardi et al, 2021), and therefore may have certain reasons to make health care use decisions. To identify potentially modifiable factors and develop appropriate interventions, more in-depth studies are needed on parent perspectives about the reasons that drive their use of ambulatory care for children at risk of maltreatment.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that very few studies have assessed ACSCs for children who have possibly experienced maltreatment, and this issue needs to be investigated further in other samples (e.g., children involved in child protective services). Relative to the general pediatric population, children with suspected maltreatment have more chronic illnesses and higher medical complexity (Azzopardi et al, 2021), and therefore may have certain reasons to make health care use decisions. To identify potentially modifiable factors and develop appropriate interventions, more in-depth studies are needed on parent perspectives about the reasons that drive their use of ambulatory care for children at risk of maltreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Children with special medical needs and medical fragility are often involved in the child protection and child welfare systems (Palusci, 2017b). Azzopardi et al (2022) found that nearly one-quarter (23.6%) of children with medical complexity had documented contact with the child welfare system, most commonly for neglect; of those, more than one-third (38.8%) were removed by CPS. Caregivers reported a history of mental health problems, chronic medical conditions, and interpersonal violence or trauma, but caregiver married/ common-law relationship status and a higher number of medical technology supports were associated with decreased likelihood of child welfare system involvement.…”
Section: Children With Medical Complexitymentioning
confidence: 99%